Early aEEG can predict neurodevelopmental outcomes at 12 to 18 month of age in VLBWI with necrotizing enterocolitis: a cohort study - Si Chen; Xiuman Xiao; Su Lin; Jianghu Zhu; Lidan Liang; Minli Zhu; Zuqin Yang; Shangqin Chen; Zhenlang Lin; Yanli Liu (BMC, 2021)
Abstract Background Studies have shown that neurological damage is common in necrotizing enterocolitis (NEC) survivors. The purpose of the study was to investigate the predictive value of amplitude-integrated electroencephalogram (aEEG) for neurodevelopmental outcomes in preterm infants with NEC. Methods Infants with NEC were selected, and the control group was selected based on 1:1-2 pairing by gestational age. We performed single-channel (P3-P4) aEEG in the two groups. The Burdjalov scores were compared between the two groups. Cranial magnetic resonance imaging (MRI) was performed several months after birth. The neurological outcomes at 12 to 18 months of age were compared with the Gesell Developmental Schedules (GDS). The predictive value of aEEG scores for neurodevelopmental delay was calculated. Results There was good consistency between the two groups regarding general conditions. In the 1st aEEG examination, the patients in NEC group had lower Co (1.0 (0.0, 2.0) vs. 2.0 (2.0, 2.0), P = 0.001), Cy (1.0 (0.0, 2.0) vs. 3.0 (3.0, 4.0), P < 0.001), LB (1.0 (0.0, 2.0) vs. 2.0 (2.0, 2.0), P < 0.001), B (1.0 (1.0, 2.0) vs. 3.0 (3.0, 3.5), P < 0.001) and T (3.0 (2.0, 8.0) vs. 10.0 (10.0, 11.5), P < 0.001), than the control group. Cranial MRI in NEC group revealed a widened interparenchymal space with decreased myelination. The abnormality rate of cranial MRI in the NEC group was higher than that in the control group (P = 0.001). The GDS assessment indicated that NEC children had inferior performance and lower mean scores than the control group in the subdomains of gross motor (71 (SD = 6.41) vs. 92 (SD = 11.37), P < 0.001), fine motor (67 (SD = 9.34) vs. 96 (SD = 13.69), adaptive behavior (76 (SD = 9.85) vs. 95 (SD = 14.38), P = 0.001), language (68 (SD = 12.65) vs. 95 (SD = 11.41), P < 0.001), personal-social responses (80 (SD = 15.15) vs. 93(SD = 14.75), P = 0.037) and in overall DQ (72 (SD = 8.66) vs. 95 (SD = 11.07), P < 0.001). The logistic binary regression analysis revealed that the NEC patients had a significantly greater risk of neurodevelopmental delay than the control group (aOR = 27.00, 95% CI = 2.561-284.696, P = 0.006). Confirmed by Spearman's rank correlation analysis, neurodevelopmental outcomes were significantly predicted by the 1st aEEG Burdjalov score (r = 0.603, P = 0.001). An abnormal 1st Burdjalov score has predictive value for neurodevelopmental delay with high specificity (84.62%) and positive predictive value (80.00%). Conclusions Children with NEC are more likely to develop neurodevelopmental delay. There is high specificity and PPV of early aEEG in predicting neurodevelopmental delay.